2019
DOI: 10.3389/fonc.2019.00819
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic Response of Leptomeningeal Carcinomatosis to Nivolumab in PD-L1 Highly Expressive Non-small Cell Lung Cancer: A Case Report

Abstract: In a patient who had been diagnosed of located squamous cell lung carcinoma, pneumonectomy, and adjuvant chemotherapy were performed. Brain recurrence and subsequent lung metastatic disease were uncontrolled by neurosurgery, holocranial radiotherapy, and first-line chemotherapy. In August 2015, appearance of leptomeningeal carcinomatosis triggered severe clinical deterioration and threatened the patient's life. Anti-PD1 immune checkpoint inhibitor Nivolumab was initiated in an attempt to stop tumor growth, ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…The search yielded 289 citations, of which 14 were included in the qualitative synthesis (Supplementary File 1). Nine were case-reports, four were retrospective case-series (including 32 patients), and one was a single-arm phase-II trial (including 20 patients); levels of evidence were V, IV, and IIb, respectively (Supplementary File 2) (8)(9)(10)(11)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). Critical appraisal resulted in low risk of bias for all included articles (Supplementary File 3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The search yielded 289 citations, of which 14 were included in the qualitative synthesis (Supplementary File 1). Nine were case-reports, four were retrospective case-series (including 32 patients), and one was a single-arm phase-II trial (including 20 patients); levels of evidence were V, IV, and IIb, respectively (Supplementary File 2) (8)(9)(10)(11)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). Critical appraisal resulted in low risk of bias for all included articles (Supplementary File 3).…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, most of our pooled patients presented with headache, vomiting, and cranial-nerve palsies, but available data on hydrocephalus were scarce. In two singular cases, memory loss and auditory hallucinations were ascribed to the presence of temporoinsular LMD lesions (8,21). Most LMD diagnoses were obtained after new symptom onset or upon routine followup surveillance in patients with metastatic disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among those drugs and therapies, programmed death-1 (PD-1)/programmed death ligand-1 (PD-L1) blockade was proved to be novel cancer immunotherapies for cancers treatment, and the associated drugs were developed to treat NSCLC in clinic [ 6 , 7 ]. These therapeutic drugs included PD-1 inhibitors Nivolumab (Opdivo) [ 8 , 9 ] as well as Pembrolizumab (Keytruda) [ 10 , 11 ], and PD-L1 inhibitors Atezolizumab (Tecentriq) [ 12 ], Durvalumab (Imfinzi) [ 13 ] and Avelumab (Bavencio) [ 14 ]. Previous data indicated that cancer cells derived PD-L1 regulated the activity of CD8 + T cell activity [ 15 , 16 ], which was a pivotal component of the cellular immune response in tumor development [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we have a hypothesis that whether SMARCA4m could be a predictor for ICIs response in NSCLC. Notably, there was one previous report that showed that PD-1 inhibitor was effective for a SMARCA4 deficient NSCLC patient with a high TMB and PD-L1 not highly expressed [9]. However, there was another study that reported hyperprogressive disease was obtained after immune checkpoint inhibitor treatment in SMARCA4 deficient SCLC [10].…”
Section: Discussionmentioning
confidence: 99%